2014
DOI: 10.12688/f1000research.4799.1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of the honeybee Apis mellifera during visual search for vertical targets presented at various heights: a role for spatial attention?

Abstract: When honeybees are presented with a colour discrimination task, they tend to choose swiftly and accurately when objects are presented in the ventral part of their frontal visual field. In contrast, poor performance is observed when objects appear in the dorsal part. Here we investigate if this asymmetry is caused by fixed search patterns or if bees can use alternative search mechanisms such as spatial attention, which allows flexible focusing on different areas of the visual field.We asked individual honeybees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…Thus in theory, bees’ flight patterns may yield different search efficiencies in environments where flowers are primarily arranged horizontally, vertically or in both planes. This is consistent with recent observations that the foraging performances of bumblebees are dependent on whether flowers are presented horizontally or vertically 57 or whether foragers approach flowers from above or from below 58 . While our study only involved analyses of search behaviour in a relatively confined space at small spatial scales (100 × 72 × 73 cm arena), there is no reason why these strategies would not be expressed in open spaces and/or at larger spatial scales, in natural conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus in theory, bees’ flight patterns may yield different search efficiencies in environments where flowers are primarily arranged horizontally, vertically or in both planes. This is consistent with recent observations that the foraging performances of bumblebees are dependent on whether flowers are presented horizontally or vertically 57 or whether foragers approach flowers from above or from below 58 . While our study only involved analyses of search behaviour in a relatively confined space at small spatial scales (100 × 72 × 73 cm arena), there is no reason why these strategies would not be expressed in open spaces and/or at larger spatial scales, in natural conditions.…”
Section: Discussionsupporting
confidence: 93%
“…If bees were simply attempting to avoid collisions with walls, we would expect loops centred at a given flower to have constant amplitude throughout the search process, at a stable distance from the walls. Second, the observation that flower size limits flower detectability is consistent with knowledge on the relatively poor visual-spatial resolution of the bee eye 58 59 and numerous previous studies of two-dimensional search behaviour by bees in the lab 11 27 28 and the field 25 . Whether and how the presence of additional floral signals, such as the volatile odours emitted by natural flowers 60 , influence these search patterns in the field remain to be tested.…”
Section: Discussionsupporting
confidence: 85%
“…Morawetz and Spaethe (2012) tracked the bees that chose artificial flowers of the rewarded colour in a vertically arranged multifloral array and suggested that flight behaviour might have played a role to shape the bees' responses, thus acknowledging that they could not fully rule out simpler explanations. A subsequent analysis of the data confirmed that bees varied the height of their flight in some of the tasks (Morawetz et al, 2014), which in line with our conclusions, and suggests that in those experiments bees reverted to simpler solutions for solving the learning task at hand. Our conclusions are further supported by a recent study in which honeybees used scanning time as an alternative, non-numerical learning strategy to solve a numerosity task.…”
Section: Discussionsupporting
confidence: 88%
“…; Morawetz et al . ). Dictamnus albus racemes display a bottom‐to‐top nectar gradient due to gender‐biased nectar production towards the older female stage flowers (Fisogni et al .…”
Section: Discussionmentioning
confidence: 97%
“…Foraging pollinator behaviour defines pollen transfer within and among plants and contributes in shaping the population genetic structure. Preferential direction of visits has been observed in several species and is due to a combination of innate behaviour and learning abilities connected to foraging experience (Iwata et al 2012;Valtueña et al 2013;Morawetz et al 2014). Dictamnus albus racemes display a bottom-to-top nectar gradient due to gender-biased nectar production towards the older female stage flowers (Fisogni et al 2011).…”
Section: Discussionmentioning
confidence: 99%